A Metabolic Approach to Examining the Potential Role of the Hexosamine Biosynthetic Pathway in Diabetes-associated Atherosclerosis - Petlura, Christina (My University, 2014)
The number of people living with diabetes worldwide is continually increasing. The majority of these people will eventually die of cardiovascular disease, the major underlying cause of which is atherosclerosis. Despite the efforts of many researchers, gaps in our knowledge still exist regarding the molecular mechanism(s) linking the two conditions. Current data suggests that the hexosamine biosynthetic pathway (HBP) may have a role in the development of hyperglycemia-accelerated atherosclerosis. About 2-3% of glucose entering a cell is diverted into this pathway where it is modified through a series of reactions to yield the end product, UDP-N-acetylglucosamine (UDP-GlcNAc); a substrate for both N- and O-linked glycosylation of various molecules. N-linked glycosylation occurs in the endoplasmic reticulum (ER) and is an important process in the maintenance of ER homeostasis. We hypothesized that a dysregulation in the HBP can ultimately trigger ER stress – an event associated with the development of atherosclerosis. We have established a method that allows us to monitor levels of UDP-GlcNAc both in cultured cells and mouse tissues through high-performance liquid chromatography coupled to mass spectrometry (HPLC-MS). Using this technique, we’ve shown that both glucosamine supplementation and overexpression of the rate limiting enzyme of the HBP, GFAT, in cultured cells results in elevated UDP-GlcNAc levels. Furthermore, glucosamine was shown to trigger ER stress. In contrast, three GFAT inhibitors that were previously identified in a high throughput screen were shown to decrease UDP-GlcNAc levels and one inhibitor, dehydroiso-β-lapachone, appears to prevent ER stress induction. Finally, we use complementary methods to show that the HBP is augmented in the livers of hyperglycemic mice. This process may play a role in the accelerated development of atherosclerosis. Together, these results provide further insight into the role of the HBP in diabetic atherosclerosis and the established methods provide a platform for the further investigation of this mechanism.
Keywords: diabetes; atherosclerosis; hexosamine biosynthetic pathway; ER stress; GFAT